Pengaruh E-SAMSAT, Penghasilan, dan Sanksi terhadap Kepatuhan Wajib Pajak - Juwita, Mariam Intan; Sutrisno, Catur Ragil; Mahmudah, Dina Amalia (Badan Perencanaan Pembangunan, Penelitian dan Pengembangan Daerah (Bappeda) Kota Pekalongan, 2023)
This research aims to evaluate the relationship among e-Samsat, income, and sanctions on vehicle tax payer compliance in the Pekalongan City Samsat Case Study. The population in this study is 562.961. Total samples used were 100 respondents which calculated with Slovin formula. Random sampling method was used to determine the samples. Data collected with questionnaire and proceed by using SPSS. The multiple linear regression analysis is used in this research. This research concludes that income and sanctions have a positive effect on vehicle tax compliance. Meanwhile, e-Samsat has no effect on motor vehicle tax compliance. Keywords: Vehicle tax compliance, income, e-Samsat, sanctions